Effect of land use change for bioenergy production on feedstock cost and water quality. (15th January 2018) - Zhong, Jia; Yu, T. Edward; Clark, Christopher D.; English, Burton C.; Larson, James A.; Cheng, Chu-Lin
Graphical abstract: Tradeoff relations between cost (TC), net grey water footprint (TGWF), and food crop area used for switchgrass production. Highlights: Perennial switchgrass can reduce nitrate loadings and improve water quality. Multi-objective optimization is applied to spatial data for switchgrass supply. Average grey water footprint of switchgrass ranges 132–146 L L −1 of ethanol. Tradeoffs between biomass costs and water quality are driven by land use changes. Cost of reducing grey water footprint in west Tennessee averages 0.94 m −3 . Abstract: Producing renewable fuel from dedicated energy crops, such as switchgrass, has the potential to generate localized environmental benefits. This study uses high-resolution spatial data for west Tennessee to quantify the effects of producing switchgrass for cellulosic ethanol on the grey water footprint (GWF), or the amount of freshwater needed to dilute nitrate leachate to a safe level, relative to existing agricultural production. In addition, the estimated cost and GWF are incorporated in a mixed-integer multi-objective optimization model to derive the efficient frontier of the feedstock supply chain and determine a switchgrass supply chain that achieves the greatest reduction in GWF at the lowest cost. Results suggest that background nitrate concentration in ambient water and the types of agricultural land converted to switchgrass production influence the extent of the GWF. The average GWF of switchgrass in the study area ranges between 131.8 L L −1 and 145.9 L L −1 of ethanol, which falls into the range of estimated GWF of other lignocellulosic biomass feedstock in the literature. Also, the average cost of reducing GWF from the feedstock supply chain identified by the compromise solution method is 0.94 m −3 in the region. A tradeoff between biofuel production costs and reduced nitrate loading in groundwater is driven by differences in the agricultural land converted to feedstock production. Our findings illustrate the energy-water-food nexus in the development of a local bioenergy sector and provide a management strategy associated with land use choices for the supply of energy crops. However, the water quality improvements associated with displacing crop with feedstock production in one region could be offset by expanded or more intensive agricultural production in other regions.